The Effect of Teacher’s Emotional Intelligence and Work Discipline Toward Teacher’s Performance - Dewi, Vita Putranti; Harapan, Edi; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this research was to assess the impact of teacher emotional intelligence and work discipline on teacher performance. A study was carried out utilizing quantitative approaches to discover this. According to the findings of this study, teacher emotional intelligence has a favorable and substantial effect on the performance of public high school teachers in the Mesuji Makmur District. This paper recommend to upgrade teacher emotional intelligence and work discipline where the school wish to have good performance of instructors.